STUDI PENCIPTAAN SENI KINETIK â€œRAMPOGANâ€ - Isnanta, Satriana Didiek; Rahman, Deni (Institut Seni Indoensia Surakarta, 2018)
The study of the creation of kinetic artwork with the title â€œRampoganâ€ focuses on the study of the creation of installation works that can move (kinetic). The purpose of this experiment-based art creation is to explore the possibilities of novelty on three aspects, namely: (1) visual rampogan aspects of the wayang kulit purwa as a representation of ideas, (2) aspects of the medium / material used and (3) mechanics aspects that can move the aesthetic elements of the work.The theme of the work in this creation study originated in Javanese cultural art, namely â€œRampoganâ€ (the puppet child who describes the dynamics of warriors leaving for war). This represents the idea of creating works about social phenomena that occur in Indonesia now, where the common life of the nation and state has been torn apart by a group of people who force the will of their groups by going down the streets.The method of creating this work uses a method of â€œartistic creationâ€ which consists of three stages of creation, namely: (1) the experimental stages related to the exploration of materials, tools and techniques. (2) the contemplation stage relating to the exploration process of several alternative metaphors that will be used in the work, and (3) the formation stage which is the process of materializing the work by considering the principle of composition and structure.The output of this creation study is the creation of a kinetic work with the title â€œRampoganâ€, scientific articles in national journals and intellectual property rights.Keywords: kinetic art, rampogan, Javanese culture